Repurposing drugs in autophagy for the treatment of cancer: From bench to bedside. Issue 7 (July 2022) - Bu, Faqian; Zhang, Jifa; Shuai, Wen; Liu, Jie; Sun, Qiu; Ouyang, Liang
Highlights: Targeting autophagy has become a hot tumor-therapeutic strategy. The drug repurposing strategy is emerging as a good option to discover new treatments. Many FDA-approved drugs exhibit autophagy regulation and tumor inhibition activities. The drug repurposing strategy in autophagy shows the prospects in cancer treatment. Abstract : Autophagy is a multistep degradation pathway involving the lysosome, which supports nutrient reuse and metabolic balance, and has been implicated as a process that regulates cancer genesis and development. Targeting tumors by regulating autophagy has become a therapeutic strategy of interest. Drugs with other indications can have antitumor activity by modulating autophagy, providing a shortcut to developing novel antitumor drugs (i.e., drug repurposing/repositioning), as successfully performed for chloroquine (CQ); an increasing number of repurposed drugs have since advanced into clinical trials. In this review, we describe the application of different drug-repurposing approaches in autophagy for the treatment of cancer and focus on repurposing drugs that target autophagy to treat malignant neoplasms.